Japanese garden design - Keane, Marc P. (Tuttle Publishing, 1996)
A landscape architect and garden designer working in Japan, Keane here offers a history of the Japanese garden over 20 centuries, showing how society, politics, religion, art, and the tea ceremony have contributed to the structure and elements of these beautiful retreats. He also includes chapters on design principles and techniques, explaining, for instance, how individual aspects such as rock, sand, plants, and bridges embody the symbolism of the gardens. This comprehensive book includes not only excellent full-color photography but detailed plans of the various types of gardens. An extensive glossary, a bibliography of books in English and Japanese, and numerous maps are also offered. The text concludes with a timetable mapping the evolution of the garden alongside events in Japanese culture and world history. Recommended for public and academic libraries.?Phillip Oliver, Univ. of North Alabama Lib., Florence